2017
DOI: 10.1002/chem.201701555
|View full text |Cite
|
Sign up to set email alerts
|

From Square‐Planar [ICl4] to Novel Chloroiodates(III)? A Systematic Experimental and Theoretical Investigation of Their Ionic Liquids

Abstract: A systematic investigation on the existence of chloroiodates formed by reaction of Cl with I Cl , apart from the well-known [ICl ] , namely [I Cl ] and [I Cl ] , was undertaken by employing theoretical as well as experimental methods. The thermodynamic stability in terms of the complexation enthalpies and Gibbs energies, and also the decomposition of the iodine(III) polyinterhalogen anions through dichlorine elimination to form iodine (I) compounds, was studied by means of DFT and ab initio quantum-chemical ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
13
0
4

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 49 publications
(79 reference statements)
2
13
0
4
Order By: Relevance
“…However, Krossing et al. investigated mixtures of [HMIM]Cl, [BMP]Cl, or [NEt 4 ]Cl with different amounts of I 2 Cl 6 . The recorded Raman spectra of [BMP]Cl and [NEt 4 ]Cl with 1.0 equiv of I 2 Cl 6 are in agreement with quantum‐chemical calculations at the RI‐MP2/def2‐TZVPP level of theory and support the assignment of [I 2 Cl 7 ] − .…”
Section: Polyinterhalogen Anionsmentioning
confidence: 61%
See 3 more Smart Citations
“…However, Krossing et al. investigated mixtures of [HMIM]Cl, [BMP]Cl, or [NEt 4 ]Cl with different amounts of I 2 Cl 6 . The recorded Raman spectra of [BMP]Cl and [NEt 4 ]Cl with 1.0 equiv of I 2 Cl 6 are in agreement with quantum‐chemical calculations at the RI‐MP2/def2‐TZVPP level of theory and support the assignment of [I 2 Cl 7 ] − .…”
Section: Polyinterhalogen Anionsmentioning
confidence: 61%
“…[Br 2 F 7 ] À was first described in 1976 by Sukhoverkhov et al, [184] who studied the BrF 3 /CsF/HF ternary system and reported the IR spectrum of the CsBr 2 F 7 phase.T he solid-state structure of CsBr 2 F 7 was reported in 2013 by Kraus et al [128] Thecentral fluorine atom bridges the two bromine atoms of the BrF 3 molecules and almost forms as quare-pyramidal structure.H owever,i nc ontrast to previous Raman spectroscopic investigations of Stein et al, [185] the structure neither shows aplanar anion, nor alinear Br-mF-Br unit. Stein et al also reported the Raman and IR spectra of MBr 3 F 10 (M = Cs,R b), which were both crystallized in 2016 by Kraus et al, [186] [129] Ther ecorded Raman spectra of [BMP]Cl and [NEt 4 ]Cl with 1.0 equiv of I 2 Cl 6 are in agreement with quantum-chemical calculations at the RI-MP2/def2-TZVPP level of theory and support the assignment of [I 2 Cl 7 ] À . Currently,n oc lear evidence for the formation of an [I 3 Cl 10 ] À anion has been obtained.…”
Section: Polyinterhalogen Anions Of Xy or Yz Coordinated To Xmentioning
confidence: 97%
See 2 more Smart Citations
“…Die Raman‐Spektren von [BMP]Cl und [NEt 4 ]Cl mit einem Äquivalent I 2 Cl 6 stimmen gut mit quantenchemischen Rechnungen auf RI‐MP2/def2‐TZVPP‐Niveau überein und stützen die Zuordnung von [I 2 Cl 7 ] − . Ein klarer Beweis für die Existenz eines [I 3 Cl 10 ] − ‐Anions liegt gegenwärtig nicht vor …”
Section: Polyinterhalogenideunclassified